Determination of Threshing Losses with a Raspbar Type Axial Flow Threshing Unit - Sessiz, Abdullah; Ülger, Poyraj (Journal of Agricultural Engineering, 2003)
Threshing process of grain crops is carried out mechanically using stationary threshing machines or conventional combine harvesters in Turkey. The study involves designing, constructing and testing an axial-flow threshing unit. Momtchill wheat was used as a test material. Threshing tests on wheat were conducted with the rasp-bar type threshing unit. Feed rates, drum peripheral speeds, concave clearances and moisture of grain were selected as independent parameters. Depending on these parameters total threshing losses were determined. Using ASAE standards and the others studies. All the evaluated parameters had significant effect on threshing losses, which were between 0.368% and 1.358%.